2012
DOI: 10.1016/j.bpj.2012.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Disassembly of Single Virus Particles Reveals Kinetic Intermediates Predicted by Theory

Abstract: New experimental approaches are required to detect the elusive transient intermediates predicted by simulations of virus assembly or disassembly. Here, an atomic force microscope (AFM) was used to mechanically induce partial disassembly of single icosahedral T=1 capsids and virions of the minute virus of mice. The kinetic intermediates formed were imaged by AFM. The results revealed that induced disassembly of single minute-virus-of-mice particles is frequently initiated by loss of one of the 20 equivalent cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 63 publications
(107 reference statements)
3
40
0
1
Order By: Relevance
“…Previous mechanical studies of VNPs have shown that the AFM tip usually removes individual structural components (16,19,26,36) after the elastic limit. In contrast, our data show that FICs induce an irreversible deformation of the structure without showing capsomeric vacancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous mechanical studies of VNPs have shown that the AFM tip usually removes individual structural components (16,19,26,36) after the elastic limit. In contrast, our data show that FICs induce an irreversible deformation of the structure without showing capsomeric vacancies.…”
Section: Discussionmentioning
confidence: 99%
“…FIC 1 responds linearly until it reaches a force of~4.8 nN, where a sharp drop of the force is registered (elastic limit). The elastic limit is ascribed to the breakage of the particle, which implies the shell cracking (35) or the loss of various capsomers (26,36). However, in this case, immediate imaging of the particle demonstrates the absence of capsomeric vacancies and a height decrease of <2 nm (Fig.…”
Section: Mechanicsmentioning
confidence: 96%
“…10 The mechanical manipulation and imaging of virus particles by Atomic Force Microscopy was used to identify kinetic intermediates predicted by simulations of assembly and/or disassembly. 11 Of direct relevance to the present work, a number of gas-phase investigations are bearing on the dynamics of conformational isomerization and kinetic trapping. Conformational distributions of bradykinin have been studied by Rizzo and co-workers, 12 showing the appearance of high energy conformers.…”
Section: Introductionmentioning
confidence: 99%
“…Comme en cryo-EM, la résolution de cette méthode est telle qu'il est possible d'observer les protubérances des protéines de structure de certains virus non enveloppés qui sont en général à symétrie icosaédrique, et d'en déterminer leur nombre de triangulation ainsi que leurs axes de symétrie [30]. En couplant la haute résolution pour l'imagerie et les expériences de nano-indentation, l'AFM permet de déterminer des effets subtils comme le rôle mécanique du génome présent au sein de la capside.…”
Section: Resultsunclassified